2021
DOI: 10.1177/23259671211039461
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgical Tenodesis for Treatment of Distal Semitendinosus Hamstring Tendon Injuries

Abstract: Background: Understanding the optimal management of distal semitendinosus hamstring injuries is critical for reducing pain, restoring preinjury function, maintaining knee stability, improving hamstring muscle strength, and minimizing the risk of complications and recurrence. To our knowledge, the outcomes of surgical tenodesis for distal semitendinosus hamstring injuries have not been previously reported. Hypothesis: Surgical tenodesis for injuries of the semitendinosus would enable return to preinjury level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Regarding distal semitendinosus injuries, Thompson et al 104 recently described a tenodesis of the semitendinosus to the semimembranosus in 13 professional athletes, noting that the athletes returned to sport at 15 6 4.6 weeks and all were participating in sport at 1-year follow-up. Distal semitendinosus injuries may also be treated by tendon excision and/or tenotomy or tendon stripping.…”
Section: Distal Hamstring Injuriesmentioning
confidence: 99%
“…Regarding distal semitendinosus injuries, Thompson et al 104 recently described a tenodesis of the semitendinosus to the semimembranosus in 13 professional athletes, noting that the athletes returned to sport at 15 6 4.6 weeks and all were participating in sport at 1-year follow-up. Distal semitendinosus injuries may also be treated by tendon excision and/or tenotomy or tendon stripping.…”
Section: Distal Hamstring Injuriesmentioning
confidence: 99%
“…Of the 18 included studies, five were case series [2, 10, 24, 34, 39] and 13 were case reports [1, 3–5, 8, 15, 18, 22, 23, 26, 32, 35, 36]. Fifteen studies assessed the RTS‐R and RTS‐T [1–3, 5, 8, 10, 15, 18, 22, 24, 26, 32, 35, 36, 39], and only three the RTS‐R [4, 23, 34]. Only three studies evaluated patient‐reported outcomes [2, 24, 39].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies assessed the RTS‐R and RTS‐T [1–3, 5, 8, 10, 15, 18, 22, 24, 26, 32, 35, 36, 39], and only three the RTS‐R [4, 23, 34]. Only three studies evaluated patient‐reported outcomes [2, 24, 39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations